ЗАМОНАВИЙ ТЕАТРНИНГ ЖАНР СОҲАСИДАГИ ИЗЛАНИШЛАРИ - Ходжаметова, Г. (SCIENCE and SOCIETY, 2021)
The problem of genre in art and cultural is at the same time a problem of looking at the work and through it the whole period under study. In this sense, the genre is a certain type of formal-semantic integrity introduced into culture with its concrete-historical definition.